Towards a progressive industrial policy for the twin transformation in the European Union: Synthesis report - Werner Raza (Austrian Foundation for Development Research (ÖFSE), 2024)
After decades of marginalization, industrial policy (IP) is back on the political agenda. While this shift in economic policy discourse in principle is to be welcomed, from a worker-oriented economic and political point of view, it is very important to carefully think about the why, how and for whom of industrial policy. What are the motivations for IP, which objectives shall be achieved, who should be the beneficiaries of IP, who shall sit at the table when it comes to taking decisions, and finally, who will be responsible for implementation? Upon the basis of an in-depth analysis of recent EU industrial policy for the Twin Transformation, the report outlines a policy agenda for the next five years that aims to accelerate an inclusive as well as effective Twin Transformation agenda.
Keywords: 330